The Analysis of Figurative Language on The Novel Tarian Bumi by Oka Rusmini: A Hermeneutic Approach - Jefriyanto Saud; Weldemina Yudit Tiwery; Bredyna Agnesiana (RETORIKA: Jurnal Ilmu Bahasa, 2023)
The Novel of Tarian Bumi is one of the novels that tells about a woman who is of a different caste than men, both related to social status, culture, injustice and violence. In this novel, Oka Rusmini uses figurative language in telling the phenomenon of caste differences between men and women.The purpose of this research is to describe the using of the kinds of figurative in the novel of Tarian Bumi by Oka Rusmini. The research method is reading hermeneutic, that is the reading which can find out the meaning of the text readed. The result of this research showed that Oka Rusmini used two figurative language categories, namely namely figure speech and elements of rhetoric. The figure of speech used by Oka Rusmini in the novel Tarian Bumi is a figure of speech of simile, metaphor, hyperbole, while the rhetorical elements contained in the novel are repetition, anaphora and parallelism. Oka Rusmini many times used figurative language in the novel of Tarian Bumi image is to unable can give the effect to the readers and the readers are curious to know the messages that delivered because figurative language has the big impression on getting the good effect to Novel of Tarian Bumi. Besides, figurative language make people easy to understands about the meaning which are contained in the novel.